ANALYSIS OF THE APPLICATION OF ISLAMIC BUSINESS ETHICS TO WOMEN ENTREPRENEURS IN JAMBI CITY - Zuhratul Aulia; Siti Rumsiah; Ahmad Ridwan; M. Nasrullah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This study discusses the Application of Islamic Business Ethics to Women Entrepreneurs in the city of Jambi, from the focus of the problem the sub-topic of the problem is described as follows: How is the concept of applying Islamic business ethics and what form of application of Islamic business ethics is exemplified by Rasulullah SAW., Women Entrepreneurs in Jambi city. The results of the study show that Islamic values such as sidiq, fatahan, amanah and tabliq have been reflected in the lives of women entrepreneurs in the city of Jambi.